Performance Evaluation of Cabbage Cultivars under Open Field Cultivation in High Altitude of Tawang Arunachal Pradesh - Tiwari, Ankit; Singh, Sunil K.; Bora, Ajitabh; Gogoi, Baikuntha J.; Dwivedi, Sanjai K. (Defence Life Science Journal, 2022)
The study has been undertaken to evaluate the performance of locally available commercial cultivars of cabbage in open field during summer season of 2019 at Defence Research Laboratory Research and Development Centre Tawang (Arunachal Pradesh). The commercial cultivars of these vegetables were evaluated based on the growth parameters and their yield performance under open field with paired row system of planting. It was found that the cultivar Green Express performance was outstanding among test edcultivars and it superseded cv. Royal Ball BC-51 and cv. Blue Jayes in terms of growth parameters as well as marketable yield (2.62 kg/m2) and biological yield (3.47 kg/m2). The cv. Royal Ball BC-86 was also found next best performing cultivar after cv. Green Express as former was at par with growth and yield parameter and harvest maturity of later. The head of cv. Green express attended harvest maturity (149.25 days) approximately one week earlier as compared to cv. Blue Jayes (155.0 days). However, the productivity of cultivars Green Express and Royal Ball BC-86 was found within the range of national average, therefore, these two cultivars could be recommended for the commercial cultivation with paired row system of planting under open field cultivation during summer season in high altitude areas of Tawang (Arunachal Pradesh).